Pengaruh Kualitas Produk, Merek Dan Promosi Terhadap Loyalitas Pelanggan Rokok - Ruly Frans Pardede; Hamdy Hadi (Postgraduate of Jayabaya University, 2015)
This study uses a quantitative approach to data collection technique using a questionnaire. The population used in this study are all customers who use tobacco products Gudang Garam International, while method of sample using accidental sampling technique is the technique of sample withdrawal by chance, so the number of samples obtained as many as 100 people. The data analysis technique used in this study is the analysis of regression and correlation. The results revealed a significant difference between the quality of the product, brand and promotion jointly on customer loyalty cigarettes Gudang Garam International. The result proved that the customer loyalty is assumed to be positively affected by the price and the service that pertain in Alakasa Extrusindo Company. The result proved that the customer loyalty was simultaneous affected by the price and service.